Two new species of the genus Dichillus Jacquelin du Val, 1861 (Coleoptera: Tenebrionidae: Stenosini) from Thailand - Schawaller, Wolfgang; Bellersheim, Aron (Zootaxa, 2022)
Two species of Dichillus Jacquelin du Val, 1861 (Tenebrionidae, subfamily Pimeliinae, tribe Stenosini) new to science from the lowlands of central Thailand are described: Dichillus grimmi sp. n. and Dichillus siamicus sp. n. An identification key for the four known species of Dichillus from Thailand is provided. A checklist of Stenosini from Thailand is added.